Building a brand portfolio: the case of English Football League (EFL) clubs. Issue 3 (4th May 2022) - Pritchard, Adrian; Cook, David; Jones, Andrew; Bason, Tom; Salisbury, Paul
ABSTRACT: Research question: Professional sports clubs (PSCs) may diversify by marketing a range of products that extend beyond sport. Using brand architecture as a framework, the research aims to examine: the brand names they adopt, markets they serve and the hierarchical relationship between the leagues and PSCs in the branding of the product ranges of both organizations. Research methods: Set within the context of the English Football League (EFL), club websites were reviewed to examine brand names that are used when marketing activities unrelated to sport. Semi-structured interviews were conducted with the commercial staff of 21 PSCs relating to their branding strategy. Results and findings: Leagues and PSCs may market a number of brands in addition to their core products of sporting competitions and teams. EFL clubs have developed brands independently of the league, primarily by branding their stadiums as a multi-purpose venue to stage events not related to matches. Within their venues they have also developed a category we term 'stadium sub-brands'. These include business clubs, comedy clubs and restaurants. Some of these services are co-branded with partner organizations. Implications: Devising a typology of the brand architecture of EFL clubs illustrates how sports organizations can diversify into markets other than football and add to their product portfolio by making use of their resources, in particular their stadium.